Competencias socio-afectivas: una exigencia para el profesor contemporáneo (2012)
Unplanned innovations have stemmed fundamentally from the use of new technologies in current societies to lead to new challenges. In this environment where knowledge is an essential in economic exchanges, a reconsideration of the nature of every productive activity is demanded. The school institution devoted to the generation and reproduction of knowledge turns out to be affected in its education methods and in its learning processes by the models of society that are emerging. The contents of learning, its conditions and references have to be in accordance with the characteristics of social changes. In this sense, one of the principal challenges, similar to the methods of learning is located around on the coordinator of educational processes understanding how he must perform his task. The teacher acquires another way of carrying out his work if it is considered that the pupil is becoming more autonomous. He has more breadth of resources to gain access to knowledge and goes through psychosocial processes where the traditional figure of the teacher is devalued. The teacher is immersed in a dynamic of production of knowledge that demands continuous innovation and aptitude. The torrent of new knowledge demands that professionals constantly update their skills. Therefore, training and professional development have become fundamental activities for making any productive task viable. Logically, one aspect of core value consists of understanding that the teacher needs to be perceived as a professional involved in a permanent learning process. This is a question to restructuring the profile of the contemporary teacher to give him affinity with today’s school requirements.